Identification of novel recombinants and proposed standard reference genomes for phylogenetic classification of canine parvovirus-2 (CPV-2): Comprehensive analysis revealing global evolutionary trait - Bahoussi, Amina Nawal; Wang, Pei-Hua; Ma, Zi-Hui; Rani, Nikita; Wu, Changxin; Xing, Li (Frontiers in Veterinary Science, 2022)
Sustained spread and continuous evolution of CPV-2 generate new genetic information; nevertheless, there is no adopted phylogenetic tool, and parvo virologists still refer to the three antigenic variants. Herein, this report attempted to review the evolutionary trait of CPV-2 and proposed standard reference genomes using the Maximum Likelihood-based phylogenetic analysis and Parsimony-Informative Sites. The analysis revealed three main evolutionary pathways where CPV-2 strains from the USA and China cluster into distinct clades depicted as GI, GII, or GIII, respectively. Furthermore, novel CPV-2 natural recombinants were detected, occurring only between the newly identified strains (2017–2020). Those findings provide unique insights into the evolutionary relatedness of CPV-2, clarify discrepancies between different geographic areas and will contribute to achieving a more reliable CPV-2 genetic and evolutionary genotyping classification.